2017
DOI: 10.1016/j.str.2017.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Maltoporin LamB Unfolds β Hairpins along Mechanical Stress-Dependent Unfolding Pathways

Abstract: Upon mechanical pulling at either terminal end, β barrel outer membrane proteins stepwise unfold β strands or β hairpins until entirely extracted from the membrane. This unique unfolding pathway has been described for β barrels comprising 8, 14, or 22 β strands. Here we mechanically unfold the 18-stranded β barrel outer membrane protein LamB from Escherichia coli. We find that its mechanical unfolding pathway is shaped by the stepwise unfolding of β hairpins. However, we also observe that β hairpins can unfold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 42 publications
2
26
0
Order By: Relevance
“…As for OmpG, ≈0.3‰ of 280528 force-distance curves recorded in the approach and retraction cycles showed a force peak pattern that resembled a saw-tooth like unfolding pattern typically found for Omps 46,48,49,51 . The majority (>90%) of these force-distance curves showed 12 predominant force peaks (Fig.…”
Section: Resultsmentioning
confidence: 58%
“…As for OmpG, ≈0.3‰ of 280528 force-distance curves recorded in the approach and retraction cycles showed a force peak pattern that resembled a saw-tooth like unfolding pattern typically found for Omps 46,48,49,51 . The majority (>90%) of these force-distance curves showed 12 predominant force peaks (Fig.…”
Section: Resultsmentioning
confidence: 58%
“…This mechanical unfolding of membrane proteins typically occurs via a series of unfolding steps, which describe the distinctive unfolding pathways taken by the protein (Kedrov et al, 2007;Oesterhelt et al, 2000;Sapra et al, 2009). Recently, Omps received particular attention by SMFS, as their mechanical unfolding pathways are tightly linked to their secondary structure (Bosshart et al, 2012a;Sapra et al, 2009;Thoma et al, 2012Thoma et al, , 2017. Commonly, the unfolding steps of transmembrane b barrel proteins are shaped by individual b hairpins, which has been observed for the 14-stranded b barrel of OmpG (Sapra et al, 2009), the 18-stranded b barrel of LamB (Thoma et al, 2017), the 19-stranded voltage-gated anion channel (VDAC) (Ge et al, 2016), as well as the 22-stranded b barrel of FhuA (Thoma et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The nitrogen regulatory protein P-II (Spot S28) is one of the most widely distributed families of signal transduction proteins widespread among bacteria, archaea, and plants (Radchenko and Merrick, 2011) and control the activities of a very diverse range of enzymes, transcription factors and some membrane transport proteins by direct interaction with their target hosts (Merrick, 2014). The maltoporin (Spot b), secreted by all the V. parahaemolyticus isolates, belongs to the outer membrane porin family of Gram-negative bacteria (Thoma et al, 2017) and is a versatile vaccine candidate in Vibrio species (Lun et al, 2014). Recently, Yang B. et al (2019) reported that the maltoporin (Spot b) also contributed to the adhesion and invasion ability of Aeromonas veronii TH0426 to epithelioma papulosum cyprini cells.…”
Section: Discussionmentioning
confidence: 99%